2018
DOI: 10.5664/jcsm.7208
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Midlife Women at the Cusp of the Menopausal Transition

Abstract: A commentary on this article appears in this issue on page 1095.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…There seems to be a positive correlation between depressive disorders and sleep disorders [31]. Vasomotor symptoms have been among the most influencing factors of sleep disturbances [32] and are also directly associated with menopause-specific quality of life [33]. Moreover, vasomotor symptoms, through the negative effect on sleep, can also influence women’s mood [34] and the sense of restlessness during the day [35].…”
Section: Mood-sleep Disturbances and Vasomotor Symptomsmentioning
confidence: 99%
“…There seems to be a positive correlation between depressive disorders and sleep disorders [31]. Vasomotor symptoms have been among the most influencing factors of sleep disturbances [32] and are also directly associated with menopause-specific quality of life [33]. Moreover, vasomotor symptoms, through the negative effect on sleep, can also influence women’s mood [34] and the sense of restlessness during the day [35].…”
Section: Mood-sleep Disturbances and Vasomotor Symptomsmentioning
confidence: 99%
“…Menopause can be accompanied by experiences such as depression, anxiety, impaired sleep quality, weakening of mood, and deterioration of focusing and memory. (Jones et al, 2018; Kim et al, 2015; Li et al, 2012; Sussman et al, 2015). Sleep complications in menopause are affected by multiple factors, such as physiological hormonal change, psychological factors, and physical sickness (Guthrie et al, 2018; Thurston et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbances and fatigue are prevalent among healthcare providers, which might result from stressful workload and rotating shifts (Gao et al, ; Korsiak, Tranmer, Leung, Borghese, & Aronson, ). Research has revealed that women report more sleep problems than men (Brown, Gallicchio, Flaws, & Tracy, ; Jones, Zak, & Lee, ; Pengo, Won, & Bourjeily, ). Female shift workers have been found to increase the risk of type 2 diabetes (Li et al, ; Pan, Schernhammer, Sun, & Hu, ), breast cancer (Grundy et al, ; Travis et al, ) and coronary heart disease (Vetter et al, ).…”
Section: Introductionmentioning
confidence: 99%